Konflik Agraria antara Masyarakat dan PT Perkebunan Nusantara sebagai Potensi Kerawanan Sosial di Jawa Barat - Kayla Mutiara Shabina; Yusa Djuyandi (Public Knowledge, 2026)
Agrarian conflict remains a structural problem in Indonesia and has the potential to become a social threat at the local level. In West Java, land disputes often involve local communities and PT Perkebunan Nusantara (PTPN) as large-scale managers, mainly due to overlapping land ownership claims between official rights and de facto control by the community. This study aims to analyze the dynamics of agrarian conflicts between communities and PTPN as a potential social vulnerability in the region using the perspectives of regional vigilance and conflict management. This study applies a qualitative descriptive method through literature review and document analysis. Agrarian conflicts between communities and PTPN often develop into latent conflicts characterized by increasing community dissatisfaction. The socio-economic dependence of communities on land intensifies the conflict and broadens its impact to the social sphere, thereby increasing the potential for regional social vulnerability. These findings confirm that agrarian conflicts can be understood as a potential social vulnerability that can be identified early on.